Evaluation of von willebrand factor during pregnancy, lactation and oestrous cycle in bitches affected and unaffected by von willebrand disease - Mattoso, Crs [UNESP]; Takahira, Rk [UNESP]; Beier, Sl; Araujo, Jp [UNESP]; Corrente, Je [UNESP] (Wiley, 2013)
Plasmatic concentrations of von Willebrand Factor (vWF) increase during pregnancy in humans and dogs; however the mechanism of such increase is still not well defined. The aims of this study were: (i) to evaluate changes in vWF concentration during pregnancy and during the subsequent oestrous cycle in bitches affected and unaffected by von Willebrand Disease (vWD); (ii) to correlate the vWF levels and cortisol levels in both groups. Seven vWD affected (GI) and nine unaffected (GII) bitches were used. The animals were assessed during pregnancy, parturition, lactation and non-gestational oestrous cycle in 11 moments (Pregnancy 1, Pregnancy 2, Parturition, Lactation 1, Lactation 2, Lactation 3, Anestrus, Proestrus, Oestrus, Diestrus 1, and Diestrus 2). The following tests were performed; measurement of von Willebrand factor antigen (vWF:Ag), albumin and cortisol. In both groups, vWF concentration remained stable during the non-gestational oestrous cycle, but increased during pregnancy, with the highest value observed at parturition. Increases of 70% and 124% in vWF were seen in GI and GII, respectively, compared to anestrus. No correlation was found between vWF and cortisol. Values of vWF:Ag changed during pregnancy, with a peak at parturition, both in vWD affected and unaffected animals. Values of vWF were not altered in the different phases of the oestrous cycle following pregnancy in both groups. Evaluation of vWF during pregnancy can cause false negative results for vWD, but assessment can be performed at any point in the oestrous cycle of non-pregnant bitches. © 2012 Blackwell Verlag GmbH.
Keywords: Animalia; Canidae; Canis familiaris